How stable are visions for protected area management? Stakeholder perspectives before and during a pandemic. Issue 2 (20th January 2022) - Lo, Veronica B. P. G.; López‐Rodríguez, María D.; Metzger, Marc J.; Oteros‐Rozas, Elisa; Cebrián‐Piqueras, Miguel A.; Ruiz‐Mallén, Isabel; March, Hug; Raymond, Christopher M.
Abstract: Envisioning processes enable protected area managers to chart a course for future management to reach desired goals, but unexpected changes that could affect future visions are not usually considered. The global COVID‐19 pandemic provided an opportunity to explore changes in stakeholder visions, the values that underpin the visions, and their perceptions of landscape changes and the underlying drivers (e.g. climate change, mass tourism and demographic trends). Through a mixed‐methods approach in this post‐evaluation study, we gathered comparative data on these issues from stakeholders in the Sierra de Guadarrama National Park, Spain, between July 2019 (pre‐pandemic) and October 2020 (mid‐pandemic). Our qualitative analysis demonstrates that pre‐pandemic, differences in visions for protected area management were largely spurred by different perceptions of drivers of change, rather than differences in values or perceived landscape changes, which were similar across different vision themes. One year later, in the midst of the COVID‐19 pandemic, the majority of stakeholders reported that their values, visions and perceptions of drivers did not change despite this large‐scale disturbance. Of the 20%–30% of stakeholders that did report changes, visions generally shifted towards greater prioritization of biodiversity and nature conservation as a result of heightened perceptions of the impacts of drivers of change associated with an increase in the numbers of park visitors. These drivers included mass tourism, mountain recreation, lack of environmental awareness, and change in values and traditions. Our findings reinforce the importance of adaptive and inclusive management of protected areas, including enhancing transparency and communications regarding factors driving change in the landscape, and integration of local and traditional knowledge and stakeholder perceptions of changes and drivers. Furthermore, management plans integrating stakeholder values have the potential to stay relevant even in the face of wildcard events such as a pandemic. To enhance the relevancy of visions and scenarios in conservation and land‐use planning, scenario planning methodologies should more strongly consider different potential disturbances and how drivers of change in the near and far future can be affected by wildcard events such as a pandemic. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: Los procesos de reflexión sobre posibles escenarios permiten a los gestores de áreas protegidas trazar un rumbo para la gestión futura con el fin de alcanzar los objetivos deseados. Sin embargo, no se suelen tener en cuenta los cambios inesperados que podrían afectar a las visiones de futuro. La pandemia mundial de COVID‐19 ha brindado la oportunidad de explorar los cambios en las visiones de futuro por parte de diferentes actores sociales, los valores que las sustentan y las percepciones de los cambios en el paisaje y de los factores subyacentes (ej. el cambio climático, el turismo de masas y las tendencias demográficas). A través de un enfoque de métodos mixtos, en este estudio de evaluación a posteriori, recopilamos datos comparativos sobre estas cuestiones en el Parque Nacional de la Sierra de Guadarrama, España, entre julio de 2019 (pre‐pandemia) y octubre de 2020 (durante la pandemia). Nuestro análisis cualitativo demuestra que, antes de la pandemia, las diferencias en las visiones de la gestión de las áreas protegidas se debían en gran medida a las diferentes percepciones de los factores de cambio, más que a las diferencias en los valores o los cambios percibidos en el paisaje, que eran similares en los diferentes temas. Un año después, durante la pandemia de COVID‐19, la mayoría de los participantes expresaron que sus valores, visiones y percepciones de los impulsores no habían cambiado a pesar de esta perturbación a gran escala. Para entre el 20 y el 30% de los participantes que sí reflejaron cambios, las visiones generalmente cambiaron hacia una mayor prioridad de la biodiversidad y la conservación de la naturaleza, como resultado de una mayor percepción de los impactos de los impulsores de cambio asociados con el aumento del número de visitantes del parque. Entre estos factores se encuentran el turismo de masas, las actividades recreativas en la montaña, la falta de concienciación medioambiental y el cambio de valores y tradiciones. Nuestros resultados refuerzan la importancia de la gestión adaptativa e inclusiva en áreas protegidas, incluyendo la mejora de la transparencia y la comunicación en relación con los factores que impulsan cambios en el paisaje, así como la integración de los conocimientos locales y tradicionales y las percepciones de las partes interesadas sobre los cambios y los impulsores. Además, los planes de gestión que integran los valores de diferentes actores sociales tienen el potencial de seguir siendo relevantes incluso ante acontecimientos imprevistos como una pandemia. Para aumentar la relevancia de las visiones y los escenarios en la planificación de la conservación y de la gestión del territorio, las metodologías de diseño participativo de escenarios de futuro deberían tener más en cuenta diferentes perturbaciones potenciales y cómo los impulsores del cambio en el futuro cercano y lejano pueden verse afectados por acontecimientos como una pandemia. Read the free Plain Language Summary for this article on the Journal blog.